EFFORTS TO OVERCOME THE CRIME OF MONEY LAUNDERING (PADANG LAWAS POLICE RESEARCH STUDY) - Ilmuwani Lubis; Karolus Agung Dery Rianto; Irfan Rizky Pradya; Willy Novan Prakoso; Stephen Martin (PT. Radja Intercontinental Publishing, 2023)
Money laundering, often known as money laundering, is carried out by government officials who hold the power to recover illegal money after getting results that do not belong to them. In Indonesian, money laundering is translated as